Is medial elbow pain correlated with cubital tunnel syndrome? An electrodiagnostic study. Issue 2 (19th June 2015) - Speach, David P.; Lee, Daniel J.; Reed, Jeffrey D.; Palmer, Bradley A.; Abt, Patrick; Elfar, John C.
ABSTRACT: Introduction : Medial elbow pain is often considered to be a symptom associated with ulnar neuropathy at the elbow (UNE). We examined the relationship between medial elbow pain and a positive electrodiagnostic (EDx) test result for UNE. Methods : We performed a retrospective review of 884 patients referred for EDx evaluation of UNE. Regression models were used to determine the odds ratios between clinical findings and a positive EDx result for UNE. Results : Patients reported medial elbow pain in 44.3% of cases. Clinical factors that correlated with a positive EDx study result for UNE included male gender, small and ring finger numbness, ulnar intrinsic weakness, and age. Medial elbow pain was negatively correlated with a positive EDx result. Conclusions : This study demonstrates a negative correlation between medial elbow pain and a positive EDx result for UNE. Medial elbow pain should not be considered a clear diagnostic symptom of UNE. Muscle Nerve 53: 252–254, 2016